ISOLATION AND IDENTIFICATION OF BRENNERIA NIGRIFLUENS AS CAUSAL AGENT OF BARK CANKER DISEASE ON WALNUT IN IRAQ - & AMIN, Al-MAAROOF (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Bark canker disease has recently found in Sulaimani province. Disease incidence reached to 17.2% in Tawella. Bacterial isolates were identified by their morphological and biochemical characteristics using the API 20E system. Fifty-one and half percent of the isolates were identified as Brenneria nigrifluens and 36.3% as Pantoea spp. B. nigrifluens isolates formed circular colonies with entire margins and creamy color on nutrient agar. Biochemical tests classify B. nigrifluens isolates into seven groups. Vitek GN system further used to confirm the identification. The isolates produced necrotic lesion of different size on artificial inoculated walnut branches, but no symptoms on detached leaves. Isolates 22, 28 and 31 induced typical symptoms on two years old seedlings. B. nigrifluens successfully re-isolated from the inoculated seedlings. All B. nigrifluens isolates were resistant to erythromycin and cephalexin, most of them (16/17) were resistant to ampicillin, (13/17) resistant to vancomycin, (12/17) resistant to rifampin and amikacin; while (10/17) were moderately resistant to penicillin; (7/17) were moderately susceptible to streptomycin and (6/17) to gentamicin. Chloramphenicol, tobramycin, and tetracycline showed high efficiency in bacterial growth inhibition. Minimum inhibitory and minimum bactericidal concentrations of five chemicals against 17 bacterial isolates showed high efficiency of Kocide in killing 94.1% and inhibiting of 100% of the isolates at 0.31g/L In vitro, followed by Nordox which kill 70.6% and inhibit 76.4% of the isolates at 0.65 and 0.32 g/L respectively. In vivo studies confirm high efficacy of Kocide in disease control and restriction of vertical and horizontal extension of the cankers followed by Nordox.